PENGARUH UKURAN PERUSAHAAN, JAMINAN OBLIGASI, UMUR OBLIGASI TERHADAP PERINGKAT OBLIGASI (Study Empiris pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia periode 2016-2018) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
This study aimed to determine the effect of Company Size, Bond Guarantees, Age of Bonds, Equity toward Bond Rates in Banking Sector Companies in the Indonesia Stock Exchange from 2016 to 2018. The number of samples used in this study consisted of 13 banking companies taken by using purposive sampling methods and the banking companies routinely issue bonds during 2016-2018 and were rated by PT PEFINDO. The data analysis method used in this study was the logistic regression model. The results of this study indicated that Company Size and Bond Guarantees affected bond ratings. Age of Bonds had no impacts on bond rates. The next researchers are expected to add other independent variables outside the variables used by researchers at this time.